Finding the Effects of Characteristics of an Urban Road on the Number of Road Accidents - Atul Soni, Deepak Varshney (International Journal of Advanced Science and Technology, 2020)
Accidents are very serious issue to society, causing loss and damage to the life and property. Accident count can be minimized by implementing road safety measures. The objective of this study is to find the effect of the characteristics of an urban road on the number of accidents, so that the direct interference of road characteristics with the number of accidents occurring can be established. A literature review was conducted and based on the literature review Negative Binomial statistical method was adopted for the study purpose. AADT of road, road width, number of accesses, the average speed of vehicles and the length of the section were used as dependent variables for the analysis while considering the Number of accidents as the dependent variable. Also the effect of changes in road characteristics is estimated in terms of the number of expected accidents on the urban road in India.